El equilibrio trabajo/vida familiar y felicidad como política pública en la Universidad Técnica de Cotopaxi - Zapata Tayupanta, Diana María (2023)
Work-life balance as well as happiness at work are cutting-edge concepts in management theory. Both concepts correspond to an approach that considers the worker as a whole and that gives relevance to aspects of his personal life as an element that must be taken into account in relation to his working life. The balance between work and family life focuses on the existence of a positive contribution in both directions: that work contributes to personal life and that, in turn, the latter contributes to work. Additionally, this research seeks to determine the relationship that exists between said balance with happiness at work.